The influence of powerlifting on pain frequency in the musculoskeletal system - Kacper Pajor; Katarzyna Weber-Nowakowska (Journal of Education, Health and Sport, 2019)
Introduction Powerlifting consists of exercises (squat, bench press, deadlift) that are corresponding to the three popular movement patterns. Working on proper functioning of muscles involved in these movements should have a positive impact on their performance in everyday life. However, on the other hand, significant workout strain may cause overloading and lead to musculoskeletal pain. Aim To determine the impact of regular powerlifting training on the movement organ functioning. Material Study group consisting of 185 people who regularly train powerlifting. Control group consisting of 193 people who declared lack of any physical activity in terms of strength training. Methods The research was conducted with the diagnostic poll method using author’s questionnaire. Results People who train experience pain in lower spine less often. There were also significant differences in the number of people experiencing pain when walking on a flat surface, lifting items from the floor, and moving objects above the eye level between the study and the control group for the benefit of the study group. There were no statistically significant differences found between these two groups regarding joint pain or the number of people who feel pain while sitting down. Discussion People who train powerlifting are less likely to experience back pain, what suggests beneficial effect of strength training on spine functioning. Powerlifting training positively affects the quality of movement during lifting objects from the floor and moving them above the eye level, but it does not have a significant influence on the frequency of pain in peripheral joints or while sitting down.